From Athens to the Blockchain: Oracles for Digital Democracy - Poblet, Marta; Allen, Darcy W. E.; Konashevych, Oleksii; Lane, Aaron M.; Diaz Valdivia, Carlos Andres (Frontiers in Blockchain, 2020)
Oracles were trusted sources of knowledge for public deliberation in classical Athens. Very much like expert and technical knowledge, divine advice was embedded in the deliberation and decision-making process of the democratic Assembly. While the idea of religious divination is completely out of place in our contemporary democracies, oracles made a technological comeback with modern computer science and cryptography and, more recently, the emergence of the blockchain as a “trust machine”. This paper reviews the role of oracles in Athenian democracy and, stemming from the renewed use of the term in computer sciences and cryptography, analyses the case of oracles in the nascent blockchain ecosystem. The paper also proposes a sociotechnical approach to the use of distributed oracles as informational devices to assist deliberative processes in digital democracy settings, and considers the limits that such an approach may face.